دراسة تحليلية إحصائية لواقع الاستثمار السياحي في سورية وأثره على التنمية - عكروش محمد; شيخ حسين صطوف; محسن زهيري علاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتمتع سورية بمقومات سياحية تجعل منها أحد المقاصد السياحية العالمية، كما تجعل من السياحة أحد المحركات الأساسية للاقتصاد السوري، إلا أن الاهتمام المتأخر بهذه الصناعة والحاجة لمزيد من الوقت للتعريف بالمنتج السياحي السوري عربياً وعالمياً، جعل دراسة واقع الاستثمار السياحي في سورية وتطوره وأثره على التنمية الاقتصادية، ذا أهمية كبيرة في إدراك أهمية هذا النوع من الاستثمارات في مقومات السياحة السورية، وبالتالي العمل على جذب هذه الاستثمارات, وما سيكون لها من أثر في زيادة الإيرادات الرافدة لخزينة الدولة، وتعدد فرص العمل المتاحة، ونمو للناتج المحلي الإجمالي, وذلك من خلال إيجاد مناخ استثماري ملائم وتكثيف حملات التسويق وتحديث القوانين والتشريعات. Syria has numerous natural sites and tourist elements, but because of problems that Syrian tourism industry had lately, there was an urgent need to re-study the requirements and needs of this industry and its effects on the economic development. Furthermore, the need for advertising for the Syrian products in the arab and international markets was one significant reason for studying the status quo of the Syrian tourism. All these above-mentioned points led to the study of tourist investment in Syria and its consequences in Economic development through the study of relationship between tourist investment and some of economic and tourist indicators. This relationship may have a part in recognizing the importance of such a kind of investment in economic development, then this leads to working on this investment through advertising for the elements of Syrian Tourist and developing roles and laws, and increasing tourist marketing.